Self-reported pregnancy exposures and placental DNA methylation in the MARBLES prospective autism sibling study - Schmidt, Rebecca J.; Schroeder, Diane I.; Crary-Dooley, Florence K.; Barkoski, Jacqueline M.; Tancredi, Daniel J.; Walker, Cheryl K.; Ozonoff, Sally; Hertz-Picciotto, Irva; LaSalle, Janine M. (Environmental epigenetics, 2016)
Human placenta is a fetal-derived tissue that offers a unique sample of epigenetic and environmental exposures present in utero. In the MARBLES prospective pregnancy study of high-risk younger siblings of children with autism spectrum disorder (ASD), pregnancy and environmental factors collected by maternal interviews were examined as predictors of placental DNA methylation, including partially methylated domains (PMDs), an embryonic feature of the placental methylome. DNA methylation data from MethylC-seq analysis of 47 placentas of children clinically diagnosed at 3 years with ASD or typical development using standardized assessments were examined in relation to: child’s gestational age, birthweight, and diagnosis; maternal pre-pregnancy body mass index, smoking, education, parity, height, prenatal vitamin and folate intake; home ownership; pesticides professionally applied to lawns or gardens or inside homes, pet flea/tick pouches, collars, or soaps/shampoos used in the 3 months prior to or during pregnancy. Sequencing run, order, and coverage, and child race and sex were considered as potential confounders. Akaike information criterion was used to select the most parsimonious among candidate models. Final prediction models used sandwich estimators to produce homoscadisticity-robust estimates of the 95% confidence interval (CI) and P-values controlled the false discovery rate at 5%. The strongest, most robust associations were between pesticides professionally applied outside the home and higher average methylation over PMDs [0.45 (95% CI 0.17, 0.72), P = 0.03] and a reduced proportion of the genome in PMDs [−0.42 (95% CI − 0.67 to − 0.17), P = 0.03]. Pesticide exposures could alter placental DNA methylation more than other factors.